SISTEM INFORMASI NILAI RAPORT BERBASIS SHORT MESSAGE SERVICE (SMS) PADA SMK TARBIYATUL QURRO - Yuliadi, Yuliadi; Maulana, Arif; Zaen, Mohammad Taufan Asri; Rosika, Herliana (STKIP Persada Khatulistiwa Sintang, 2024)
Exams can assess learning outcomes or measure a person's ability level during learning activities. Such conditions are considered less effective because they have to increase the number of questions, and teachers must correct students' answers individually. This study aims to create a website-based online exam information system using a MySQL database at SMK Unwanul Falah. The information collection techniques used are observation, interviews, and literature studies, while the development method is the waterfall method with stages, namely requirements, design, implementation, verification, and maintenance. The results of this study are an internet-based Online Exam Information System that is used as a supporting facility for online exams. With this online exam information system, students can take exams online with faster exam results in terms of time. The exam process does not need paper answer sheets to save costs, especially for paper stationery issued by the school. This information system helps teachers correct answers because the results will be automatically displayed after the exam.